Formation of an amorphous carbon nitride/titania composite for photocatalytic degradation of RR4 dye. (June 2020) - Azami, M.S.; Ismail, K.; Ishak, M.A.M.; Zuliahani, A.; Hamzah, S.R.; Nawawi, W.I.
Highlights: Amorphous carbon nitride/titania composite was fabricated via a facile microwave method. Amorphous carbon nitride was coated on TiO2 surface with 2.5–3.9 nm thicknesses. The a-C3N4 in the composite was acted as an e − injector and also as the e − scavenger. The photodegradation rate was 5.3 faster that TiO2-P25 under degradation of RR4 dye The photodegradation rate was equivalent to the e − -h + recombination rate from PL intensity Abstract: A composite of amorphous carbon nitride and titanium dioxide (a-C3 N4 /TiO2 ) has been successfully synthesized using urea and P25-TiO2 under microwave irradiation. The characterizations suggested that the carbon nitride component of the a-C3 N4 /TiO2 composite prepared sample is the best described as amorphous like structure containing carbonyl and amine functionality. This amorphous carbon nitrite (a-C3 N4 ) is coated on TiO2 surface with 2.5–3.9 nm of thin thickness layer detected by HRTEM. The low bandgap energy of a-C3 N4 in a-C3 N4 /TiO2 induce this amorphous acted as electron injector. The a-C3 N4 /TiO2 provide a lower electron-hole recombination as compared with P25-TiO2 base PL intensity. The photocatalytic activities of a-C3 N4 /TiO2 and P25-TiO2 were compared for the photodegradation of the dye reactive red 4 (RR4) under low intensity visible light irradiation source (273 W m −2 ). The photocatalytic degradation of RR4 for a-C3 N4 /TiO2 was degrade completely within 60 min under visible light irradiation, approximately 5.3 times faster than P25-TiO2 . This almost equivalent to their electron-hole recombination rate based on PL intensity. The hybridization of these two semiconductors have shown some improvement photocatalytic activity under visible light irradiation that influenced from the low bandgap energy of a-C3 N4, which can act as an electron injector and electron hole recombination inhibitor.